Revisiting Online Worship: John Calvin's Theology in the Digital Age - Putrawan, Bobby Kurnia; Tandana, Ester Agustini (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
This study aims to explore the relationship between the doctrine of the Trinity and three key aspects of Christian life: contemplation, community, and compassion. The Trinitarian doctrine, which describes the relationship between the Father, Son, and Holy Spirit in one divine essence, forms the foundation for understanding a relational and transformative spiritual life. The purpose of this study is to demonstrate how the concept of the Trinity is applied in the everyday life of Christians, particularly in practices such as contemplation that draws one closer to God, building church communities that reflect unity and diversity, and engaging in bold acts of compassion toward others. The methodology involves a theological literature review with a focus on systematic theology and pastoral application, as well as practical analysis of how Trinitarian teachings are implemented within the church and broader society. The results show that contemplation, community, and compassion are not only theological concepts but are actively practiced in ways that connect Christians to the Trinitarian life. By living out the teachings of the Trinity, Christians are invited into relational support, reflecting God's love, and transforming the world through courageous and sacrificial acts of love. This study contributes by providing a theological framework that connects the doctrine of the Trinity with Christian practices of contemplation, community, and compassion, offering both spiritual insights and practical applications for living out Trinitarian love in everyday life.